Teleneurology via tablet technology: an effective low-cost method to increase healthcare accessibility - Kelly Harper; Claire Hanson; Bryan Eoff; Derek Riebau; David Charles (James Cook University, 2023)
Introduction: Telemedicine is a valuable tool to increase access to health care, especially for patients in rural areas who need to visit a specialist. In place of telemedicine robots, which are costly and complicated, hospitals have implemented successful telemedicine programs using lower-cost tablet technology; opting for tablet technology increases the organizational feasibility of a large-scale telemedicine program. Methods: Vanderbilt University Medical Center (VUMC), in Nashville, Tennessee, USA, launched its teleneurology network program in 2014 to serve patients in surrounding community hospitals who needed a neurology consult. Consults are conducted using an iPad, including examinations and the secure sharing of images and patient information. This article reports on teleneurology consult data and the results of patient and physician satisfaction surveys. Results: Between February 2014 and November 2021, the VUMC teleneurology network program provided consultations for 14 241 patients with a wide variety of neurological diagnoses presenting to 12 community-based hospitals. Patient and community physician satisfaction surveys showed that 96% of physicians were satisfied with the overall care provided, and 89% of patients reported that the telehealth visits met their medical needs. Conclusion: One of the goals of telemedicine programs is to increase access to care. Therefore, it is important that the technology used to implement the program also be accessible in terms of cost and complexity. Tablets are low-cost technology, and their use in telemedicine has been shown to satisfy both physicians and patients with a wide variety of diagnoses.